Cat's Liver Disease Detection with SGOT and SGPT Evaluation as a Gold Standard Diagnosis - Kurnia Desiandura; Asih Rahayu; Freshinta Jellia Wibisono (Institute of Topical Disease Universitas Airlangga, 2022)
SGOT and SGPT are two enzymes found in the liver in large amounts. Therefore, elevated levels of these two enzymes in the blood indicate liver disease. This study aims to identify liver disease in cats in Surabaya through the levels of SGOT and SGPT in the blood as the gold standard of diagnosis. Samples came from stray cats and domesticated cats of random age, breed, and sex. The blood samples collected were 62 samples, consisting of 33 domestic cats and 29 samples from stray cats. This study showed that from 33 samples of domesticated cats, 19 samples had higher than normal levels of SGOT, and from 29 samples of stray cats, 27 samples had higher than normal levels of SGOT. For SGPT levels, from 33 samples of domesticated cats, six samples had higher than normal levels of SGPT, and from 29 samples of stray cats, six samples had higher levels of SGPT than average. Data analysis used an independent sample t-test with SPSS for Windows with a signiï¬ cance level of 0.05. The data analysis results showed no signiï¬ cant diï¬€ erence, which means that the high levels of cat SGOT and SGPT enzymes did not signiï¬ cantly aï¬€ ect the origin of the cat. Therefore, it can be concluded that high levels of SGOT and SGPT as the gold standard for detecting liver diseases can occur in all cats, including stray cats and domesticated cats.